Pendekatan “Kasih Sayang" dalam Pembelajaran Bahasa Arab di Pondok Pesantren - Fatoni, Muamar; Maghribi, Hamdan; Qosim, Muhammad Nanang (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research was motivated by the results of a survey of researchers at the Islamic boarding school Majlis Tafsir Al-Quran Mojogedang, which applies the Kuliiyatul mu'alliminal Islamiyah (KMI) system, which requires students to discipline in official languages combined with the philosophy of the "Compassion" approach in formal and non-formal teaching and learning processes. This study aims to describe the pattern of the "Compassion" approach in Arabic learning in this cottage. Descriptive qualitative research with field research methods is used to achieve this goal. The subjects in this study were lodge leaders, KMI directors, teachers' Language Section (LAC), santri Language Section (CLI). Data is collected through observations, interviews, and documentation after the data is obtained, analyzed, and conclusions are drawn. The conclusion drawn from this study is that the Compassion Approach in language learning has been the foundation since the beginning of the Language learning system, starting from Planning, Organizing, Actuating, controlling, and Evaluating, the formation of a mature language system is the love of the lodge towards the students represented by the entire Language Advisory Board. Language activities such as Ilqa al-Mufrodāt, Muḥādaśah, Muḥādarah, Language Court, and Language Extracurricular Activities have become a means of "affection" for students in MTA Islamic boarding schools where these activities there is a pattern of compassion education patterns that have been arranged in such a way as responsibility, example, and non-violence.